2012
DOI: 10.1371/journal.pone.0046694
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy Adds Complementary Detail to the High-Resolution X-Ray Crystal Structure of Photosynthetic PsbP from Spinacia oleracea

Abstract: Raman microscopy permits structural analysis of protein crystals in situ in hanging drops, allowing for comparison with Raman measurements in solution. Nevertheless, the two methods sometimes reveal subtle differences in structure that are often ascribed to the water layer surrounding the protein. The novel method of drop-coating deposition Raman spectropscopy (DCDR) exploits an intermediate phase that, although nominally “dry,” has been shown to preserve protein structural features present in solution. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…These residues are not resolved in the current PsbP crystal structure (12). Our results indicate that these residues are not exposed to the bulk solvent.…”
Section: Radiolytic Footprinting Identifies Shielded Domains On Psbp Andmentioning
confidence: 57%
See 1 more Smart Citation
“…These residues are not resolved in the current PsbP crystal structure (12). Our results indicate that these residues are not exposed to the bulk solvent.…”
Section: Radiolytic Footprinting Identifies Shielded Domains On Psbp Andmentioning
confidence: 57%
“…This information places strong constraints on the possible structures PsbP can assume in the bound state. It should also be noted that one pair of cross-linked residues, PsbP: 40 K and PsbP: 155 K, appears in the crystal structure of unbound PsbP to be separated by 14.3-16.3 Å (including rotamers) (12). The observed crosslinking of these residues with BS3 (span of ≤11.4 Å) when PsbP is bound to the photosystem indicates that a conformational change of 3-5 Å occurs in this region of the protein upon binding of the subunit to the PS II complex.…”
Section: Resultsmentioning
confidence: 99%
“…It had earlier been demonstrated that the N-terminal 19 amino acids of PsbP were critical for stable binding and promotion of oxygen evolution activity ( [168,169]; for a review of the structural and functional characteristics of PsbP, see [50,158]). This important domain on PsbP, however, is not resolved in the available crystal structures [23,24,170]. Additionally, while PsbP and PsbQ were proposed to directly interact, neither protein is in direct contact with PsbO;both, however, appear to interact with CP 26.…”
Section: Location Of Psbp and Psbq In Photosystem IImentioning
confidence: 98%
“…Interestingly, the PsbP and PsbQ proteins in green plants seem to have evolved from CyanoP and CyanoQ in cyanobacteria, although considerable genetic and functional modifications have occurred to generate the forms of these proteins seen in eukaryotes today (11). The high resolution structures of isolated PsbP and PsbQ proteins have been reported (12)(13)(14)(15). Furthermore, their locations and binding topologies in the green plant PSII complex have been proposed (16,17), but these have not been confirmed experimentally.…”
Section: Photosystem II (Psii)mentioning
confidence: 99%